MODELING OF FORM-BUILDING CURVILINEAR PROFILE FOR POLISH - V.N. ANANCHENCO; A.I. ANANCHENCO; I.C. TSIBRY; V.V . GOLOVKIN (Advanced Engineering Research, 2007)
In article is described the mathematical model of form-building curvilinear profile for polish. The model take into account nonlinear operators of transformation and nonstationary accidental influences.